An integrated approach to understanding Corvus splendens’ invasive behaviour, genetic dynamics, and ecological impact for its strategic management - Al-Obaidi, Mazen M Jamil; Al Afifi, Zakiya; Dzaraly, Nurul Diana; Muthanna, AbdulRahman; Mohd Desa, Mohd Nasir; Lani, Mohd Nizam; AlRawahi, Qais; AlAkzami, Suleiman; Al-Nadhairi, Rahma; Al-Shukaili, Ahmed; Al-Omairi, Zeyana; Akak, Mohammed; et al. (Springer Science and Business Media Deutschland GmbH, 2025)
The Indian house crow (Corvus splendens) is a species that has rapidly disseminated across Europe, the Middle East, Eastern Africa, the islands in the Indian Ocean, East Asia, Australia, and the Americas, significantly expanding its ecological range. Corvus splendens is a significant invasive species with a diminished genetic diversity due to founder effects. Its reliance on human waste in urban environments increases its ability to spread germs. The crow is ecologically versatile, thriving in anthropogenic environments and consuming waste, thereby promoting its rapid proliferation and competition with indigenous avian species. It uses urban structures for nesting and communal roosting, demonstrates resistance to noise, and assembles near human settlements for food. The present review synthesised information from multiple articles to offer a full overview of C. splendens, with a particular focus on genetic research, its pathogenicity, ecological roles, and behaviour. The main goal of this study was to provide significant insights and describe research gaps for the efficient management of this invasive species.